2017
DOI: 10.21829/myb.2017.2331418
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of nursery inoculated Fraxinus uhdei in acrisol gullies

Abstract: Presence of degraded soils is increasing worldwide, but in many scenarios the knowledge to undertake restoration has not been acquired in an efficient, economical and socially acceptable manner. There are estimates placing moderate to severe degradation of agricultural land worldwide at 80%. Severely degraded substrates, such as gullies, sometimes lack the necessary microbiota for appropriate plant growth, under these conditions nursery inoculation can improve plant performance in the field. In order to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…While it has been successful in some scenarios (Baez‐Perez et al. , Cortese and Bunn ), other studies have shown a lack of effect (Sykorova et al. , St‐Denis et al.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been successful in some scenarios (Baez‐Perez et al. , Cortese and Bunn ), other studies have shown a lack of effect (Sykorova et al. , St‐Denis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Los tratamientos de inoculación fueron de 2.5 × 10 5 y 1 × 10 6 esporas/ planta. Estudios previos determinaron que estas dosis son apropiadas para lograr la micorrización de las plantas de fresno (Báez-Pérez et al 2017). La micorrización se evaluó con la técnica de azul de tripano a una concentración de 0.05 % por 48 h, descrita por Báez-Pérez et al (2015).…”
Section: Preparación De Inóculo E Inoculaciónunclassified